The geography and causes of food insecurity in developing countries - Smith, Lisa C.; Elobeid, Amani; Jensen, Helen H. (Wiley, 2000)
At the 1996 World Food Summit, 186 countries made a commitment to reduce the number of chronically undernourished people by half by 2015. In order to formulate effective policies for reaching this goal, a thorough understanding of the location and causes of food insecurity is needed. This paper provides a broad overview of the current character of food insecurity in developing countries, focusing on two questions: (1) Why are they food insecure? and (2) Why are the food insecure? To answer the latter question data from 58 developing countries with high prevalences of food insecurity are employed to examine the relative importance of two of food insecurity's most basic causes: national food availability and the inability of people to access food due to poverty. Using child malnutrition as a proxy (along with descriptive controls for non-food determinants of malnutrition), the paper finds little correlation between national food availabilities and food insecurity. The group of countries that exhibit the highest severity of food insecurity are those with high poverty and food (dietary energy) surpluses, consistent with the view that poverty is the most widespread cause of food insecurity in the 1990s. The paper concludes by considering the implications of the analysis for appropriate geographical and policy targeting to improve food security for the greatest numbers of people at the fastest pace, now and into the 21st century.